Prospective evaluation of automatized PF4/heparin immunoassays HemosIL HIT‐ab (PF4‐H) for the diagnosis of heparin‐induced thrombocytopenia. (15th July 2014) - Jourdy, Y.; Nougier, C.; Rugeri, L.; Bordet, J. C.; Sobas, F.; Negrier, C.
Summary Introduction Recently, rapid immunoassays have been developed to allow the detection of antibodies anti‐PF4/heparin. In this prospective study, we evaluated the performances of a automatized immunoassay (HemosIL HIT‐Ab) in comparison with an ELISA (Zymutest HIA IgG) used for the diagnosis of heparin‐induced thrombocytopenia (HIT) in association with the 4T's score. Methods According to the 4T's score, samples with score ≤3 had no further analysis. Two immunological assays Zymutest HIA IgG and HemosIL HIT‐Ab were performed in samples with score ≥4. In patients with at least one positive immunological assay or two negative immunological assays but with high‐pretest probability (4T's score ≥6), HIT was screened by one functional assay using washed platelets. Results The sensitivities of both assays were excellent and comparable (100%). The specificity was 92.3% for ELISA and 91.2% for HemosIL HIT‐Ab. The analysis of the operating characteristics showed that both assays have almost identical ROCs (AUROC, 0.9951 and 0.9853, respectively, for ELISA and HemosIL HIT‐Ab) and the calculating of the κ coefficient revealed a good agreement (0.67). Conclusion Performance characteristics of the HemosIL HIT‐Ab are comparable to the Zymutest HIA IgG. The HemosIL HIT‐Ab can be used in association with the 4T's score to rule out HIT.